(untitled) (Eurasian Medical Research Periodical, 2023)
Oral parasites usually parasitize the main part of the digestive system of sick people and damage the normal life of the host organism, that is, they affect the mucous membranes of the oral cavity, swelling of the gums causes various sores and rashes in the mouth, harmful affects the normal formation and development of teeth, in turn, chewing processes. In order to protect against such parasites, it is necessary to observe the rules of personal hygiene, to wash hands before directly eating fruits and vegetables, and to pay attention to the accumulation of dental caries, tartar, and other changings in oral cavity.